Winning Essay of VIII Price Enrique Ruano Casanova: The Principle of Legality in Criminal Law and How it is Subjectively Shaped in the European Regional System of Coverage of Human Rights - Ayala González, Alejandro (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2017)
This article looks into the case law development of article 7 of the European Convention for the Protection of Human Rights and Basic Freedoms made by the European Court of Human Rights, where the principle of legality in Criminal Law appears. Once referred to the historic origins of the principle, we study its content and scope from the point of view of contrasted law. Next we look into the shaping given to the principle in the European regional system for the Protection of Human Rights. First, we study the rules of statute law and lex certa regarding the concept of law as seen in the convention. After that, we analyze the subprinciple of the prohibition of retroactivity, as well as the boundaries the latter has.
Keywords: The principle of Legality in Criminal Law; nullum crimen; nulla poena sine lege; European Agreement for Human Rights; European Court of Human Rights.